Repercussions of COVID-19 pandemic on life of men self-employed worker (Research, Society and Development, 2021)
Objective: to comprehend the repercussions of the COVID-19 pandemic on the lives of men who are self-employed professionals. Method: qualitative, action-participant study, based on Paulo Freire's theoretical and methodological framework. The Virtual Culture Circle was used, establishing an analogy between the stages of the Freirean Research Itinerary and the car, corresponding to: Thematic Investigation to the bodywork; Engine encoding and decoding; Critical unveiling of tires. In July 2020, a Culture Circle was held with the participation of 15 men self-employed worker, from different regions of Brazil, that were included by the Snowball method. Results: Thematic Research resulted in two generating themes. The first, COVID-19's fears, highlighted economic issues of the participants, the country, repercussions on the future and the fear of losing loved ones. The second theme, impacts of COVID-19 on men's health, revealed the effects on mental health, living as a couple, weight gain, hopelessness and other concerns. Conclusion: the themes expose the menace of the pandemic to hegemonic masculinity, which is forbidden to feel vulnerable and insecure. The Virtual Culture Circle created a space of care for men to talk about themselves and their lives.